2017
DOI: 10.12688/f1000research.11337.1
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa: an update on connecting the tracts

Abstract: Hidradenitis suppurativa (HS) is a devastating disease involving abscesses, sinus tracts, and inflammation classically affecting the axilla, groin, and/or anogenital region. Although the disease pathogenesis is not fully understood, recent advances suggest that HS pathology runs much deeper than the cutaneous manifestations. It is now believed that HS is a systemic inflammatory disease that gives rise to the characteristic cutaneous manifestations. This disease is problematic for both patients and physicians t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 134 publications
(172 reference statements)
2
44
0
1
Order By: Relevance
“…Patients with HS were younger, and more likely to be black, uninsured and admitted during the autumn and summer months. We observed higher rates of HS in female inpatients, which appears to be consistent with previous findings that women are more likely to have HS, especially during puberty when the secretory activity of apocrine glands is increased . A previous retrospective cohort study found the incidence of HS to be higher in female patients, particularly younger female patients and in African Americans .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with HS were younger, and more likely to be black, uninsured and admitted during the autumn and summer months. We observed higher rates of HS in female inpatients, which appears to be consistent with previous findings that women are more likely to have HS, especially during puberty when the secretory activity of apocrine glands is increased . A previous retrospective cohort study found the incidence of HS to be higher in female patients, particularly younger female patients and in African Americans .…”
Section: Discussionsupporting
confidence: 91%
“…We observed higher rates of HS in female inpatients, which appears to be consistent with previous findings that women are more likely to have HS, especially during puberty when the secretory activity of apocrine glands is increased. 32,33 A previous retrospective cohort study found the incidence of HS to be higher in female patients, particularly younger female patients and in African Americans. 34 Higher rates of admission in the summer months may be related to heat and sweating.…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis suppurativa is a chronic debilitating disease with a social and psychosocial impact . It is characterized by recurrent abscesses, draining sinus tracts, and scarring with a predilection for intertriginous skin folds . The lesions are painful and can drain malodorous fluid, leaving patients uncomfortable and self‐conscious .…”
Section: Introductionmentioning
confidence: 99%
“…What is also required is a nuanced view of the role of B cells as multifaceted and involved in not only autoantibody production but also fibrosis, stromal remodelling and (possibly) therapeutic response. IL‐6 levels correlate with loss of response to infliximab therapy [55] and given effector B‐cell contribution to IL‐6 levels in lesional tissue [24,31] along with the documented reduction in relative clinical response to TNF antagonists in advanced disease, [56] effector B‐cell function may have therapeutic relevance in the setting of advanced disease. Research gaps in the role of B cells in HS include the relative prevalence of B cell infiltrates in disease, the presence of antibodies against cutaneous structures and microbionts and exploration of B‐cell/T‐cell interactions in TLOs in HS.…”
Section: B Cells Are Unlikely To Be Primarily Pathogenic But May Indmentioning
confidence: 99%